Identification of Secondary Metabolites of Kirinyuh Leaves (Chromolaena odorata L.) as Antibacterial Using GS-MS - grasella, martha; Sulistyarini Gultom, Endang (JURNAL BIOSAINS, 2025)
This study aims to determine the minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) against pathogenic bacteria and to determine secondary metabolites in kirinyuh leaves (Chromolaena odorata) using the GC-MS (Gas Chromatography-Mass Spectroscopy) method. The test bacteria used were Escherichia coli, Staphylococcus aureus, Pseudomonas aeruginosa. The extraction method was carried out by maceration using 96% ethanol solvent. The crude ethanol extract of kirinyuh leaves in this study used concentrations of 30%, 40%, 50%, 60% and 70%. Using a UV-VIS spectrophotometer, the most effective concentration in inhibiting and killing the growth of Escherichia coli, Staphylococcus aureus and Pseudomonas aeruginosa bacteria was a concentration of 70%, with an average OD (absorbance) value of -0.2029, -0.055, and -0.0523. Then secondary metabolite identification was carried out using GC-MS (Gas Chromatography-Mass Spectroscopy) ethanol-water (9:1). The test results showed that a concentration of 70% was the most effective in inhibiting and killing Escherichia coli, Staphylococcus aureus and Pseudomonas aeruginosa bacteria. The content of secondary metabolites in the ethanol extract of kirinyuh leaves contains 33 secondary metabolite compounds, 6 of which are dominant compounds as antibacterials.